2008
DOI: 10.1007/s11676-008-0039-y
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and application of cationized pulp fiber as a papermaking wet-end additive

Abstract: Cationized pulp fibers (CPF) were prepared by the adsorption of a novel biodegradable cationic ester quaternary ammonium salt (31441) on bleached softwood kraft pulp fibers. The optimized conditions for the CPF preparation were: 4% of 31441 (based on oven-dry pulp), 80°C and 30 min. The CPF was characterized by FT-IR, SEM and XPS. Experimental results showed that the CPF improved the retention of precipitated calcium carbonate (PCC) filler significantly. With 0.9% CPF (based on oven-dry pulp), the retention of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Their advantages are low cost, biodegradability and low toxicity [ 3 , 4 ]. Cationized celluloses and other polysaccharides have been studied intensively in recent decades as flocculants, paper additives, hair care products and absorbent materials [ 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their advantages are low cost, biodegradability and low toxicity [ 3 , 4 ]. Cationized celluloses and other polysaccharides have been studied intensively in recent decades as flocculants, paper additives, hair care products and absorbent materials [ 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural polymers, such as cellulose fibers, chitosan, starch, etc., have been modified by cationization and used as strength agents in papermaking to improve the specific bond strength or increase the bonding area (Wei et al 2008;Ma et al 2010). Montplaisir et al (2006a,b) reported that the cationization of thermo-mechanical pulp fibers as softwood thermo-mechanical pulp (TMP) fibers grafted with a quaternary ammonium group improved the strength of papers and the adsorption of fines on fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Montplaisir et al (2006a,b) reported that the cationization of thermo-mechanical pulp fibers as softwood thermo-mechanical pulp (TMP) fibers grafted with a quaternary ammonium group improved the strength of papers and the adsorption of fines on fibers. In another study, Wei et al (2008) investigated the application of cationized pulp fibers as a papermaking wetend additive. They found that the tensile strength of papers was improved by 12% when 0.9% cationized softwood fiber was added to wheat straw soda pulp, and no noticeable effect was found on the stock drainage.…”
Section: Introductionmentioning
confidence: 99%
“…The cationic modification makes the fiber surface positive charged; therefore, the addition of cationic fiber results in high filler retention, well drainage property, and strong ability of absorbing anion distracters [8]. In recent ten years, this method has been paid more and more attention in papermaking industry, Xie and coworkers investigated the cationic modified fibers, which can improve the retention rate of Precipitated Calcium Carbonate (PCC), with an added proportion of 0.9%, and the retention rate increased from 57.73% to 72.21%, with the turbidity of white water decreased at the same time [21]. Cationized cellulose fibers improved strength and adsorption of anionic fines and fillers by increasing positive charges on fiber surface [20].…”
Section: Introductionmentioning
confidence: 99%